Analisis Tingkat Kesehatan Bank dengan Menggunakan Metode CAMELS pada PT. Bank Pembangunan Daerah Jambi Periode 2015-2019 - Ellys Agustina; Panji Jiblathar (Mathematical Sciences and Applications Journal, 2023)
The structured and integrated management of economic resources has a significant impact on a nation's economic growth. Banks, as crucial financial institutions, play a pivotal role in the stewardship of these economic resources. This article delves into an analysis of the banking health level using the CAMELS method for PT. Bank Pembangunan Daerah Jambi during the period from 2015 to 2019. The CAMELS method is employed to evaluate the bank's health across various indicators, encompassing Capital, Asset Quality, Management, Earnings, Liquidity, and Sensitivity to Market Risk. This assessment holds paramount importance given the micro and macro economics ramifications that banks exert on the economy. The analysis reveals that PT. Bank Pembangunan Daerah Jambi during the aforementioned period falls within the "Healthy" category based on CAMELS ratios. The Capital Adequacy Ratio (CAR) consistently exceeds 8%, and asset quality (Kualitas Aktiva Produktif - KAP) remains in a favorable category. The bank's management displays robust performance, with a commendable Net Profit Margin (NPM). Furthermore, the Return on Assets (ROA) also demonstrates a commendable performance. The bank maintains adequate liquidity with an appropriate Loan-to-Deposit Ratio (LDR). This analysis aids in assessing the bank's health and provides a deeper understanding of how it manages resources and risks. Consequently, PT. Bank Pembangunan Daerah Jambi appears to exhibit solid performance during this period, contributing to the economic stability of Jambi Province.